PENGARUH INDEPENDENSI, PROFESIONALISME, TINGKAT PENDIDIKAN, ETIKA PROFESI, PENGALAMAN, DAN KEPUASAN KERJA AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - futri, Septiani; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 8 No 1 (2014), 2014)
The purpose of this study was to determine the effect of independence , professionalism , level of education , professional ethics , experience , and job satisfaction of auditors on audit quality in the public accounting firm in Bali . The data used in this study are secondary data from a list of names public accounting firm and the primary data in the form of a respondent's answers from questionnaire data collection . This study used a simple random sampling method in the determination of the sample and there were 36 samples that meet the criteria . This study used multiple linear regression analysis for the data analysis technique , in which the results showed variable independence , professionalism , level of education , professional ethics , experience , and job satisfaction simultaneously affect auditors on audit quality . Partially, only the level of education and professional ethics have a significant effect on audit quality .
Keywords: independence , professionalism , level of education , professional ethics , experience , and job satisfaction of auditors